Developmental Differences in Neocortex Neurogenesis and Maturation Between the Altricial Dwarf Rabbit and Precocial Guinea Pig - Kalusa, Mirjam; Heinrich, Maren D.; Sauerland, Christine; Morawski, Markus; Fietz, Simone A. (Frontiers in Neuroanatomy, 2021)
Mammals are born on a precocial-altricial continuum. Altricial species produce helpless neonates with closed distant organs that are incapable of locomotion, whereas precocial species give birth to well-developed young that possess sophisticated sensory and locomotor capabilities. Previous studies suggest that distinct patterns of cortex development differ between precocial and altricial species. This study compares patterns of neocortex neurogenesis and maturation in the precocial guinea pig and altricial dwarf rabbit, both belonging to the taxon of Glires. We show that the principle order of neurodevelopmental events is preserved in the neocortex of both species. Moreover, we show that neurogenesis starts at a later postconceptional day and takes longer in absolute gestational days in the precocial than altricial neocortex. Intriguingly, our data indicate that the dwarf rabbit neocortex contains a higher abundance of highly proliferative basal progenitors than the guinea pig, which might underlie its higher encephalization quotient, demonstrating that the amount of neuron production is determined by a complex regulation of multiple factors. Furthermore, we show that the guinea pig neocortex exhibits a higher maturation status at birth, thus providing evidence for the notions that precocial species might have acquired the morphological machineries required to attain their high functional state at birth and that brain expansion in precocial newborn is largely due to prenatally initiating processes of gliogenesis and neuron differentiation instead of increased neurogenesis. Together, this study reveals important insights into the timing and cellular differences that regulate mammalian brain growth and maturation and provides a better understanding of the evolution of mammalian altriciality and presociality.